TERAPI DZIKIR UNTUK MENINGKATKAN KETENANGAN HATI PADA PENGGUNA NAPZA - Olivia Dwi Kumala; Ahmad Rusdi; Rumiani Rumiani (Universitas Islam Indonesia, 2019)
Drug users under rehabilitation and substance withdrawal frequently feel fear of their future and being rejected by society and family, and guilty to themselves and God. Such condition then leads the drug users to feel the negative emotions and discomfort. This research was conducted to observe the effectiveness of dhikr therapy to enhance the sobriety of drug users undergoing rehabilitation. Eight former drug users were involved in this study and divided into two groups: the experimental group (n = 4) and the control group (n = 4). The study design used was a pre test post test control group design and measured three times (pre test, post test, and follow up for two weeks). The measuring instrument used in the study was Tatmain al Qulub (TQS) by Rusdi (2018) in which it was compiled based upon the aspects in sobriety. The results of this study showed a significant change in sobriety among the drug users after being given dhikr therapy.